Distribution, patchiness, and behavior of Antarctic zooplankton, assessed using multi-frequency acoustic techniques - Lawson, Gareth L (Massachusetts Institute of Technology, 2006)
Thesis (Ph. D.)--Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Dept. of Biology; and the Woods Hole Oceanographic Institution), 2006. Includes bibliographical references (p. 297-311). The physical and biological forces that drive zooplankton distribution and patchiness in an antarctic continental shelf region were examined, with particular emphasis on the Antarctic krill, Euphausia superba. This was accomplished by the application of acoustic, video, and environmental sensors during surveys of the region in and around Marguerite Bay, west of the Antarctic Peninsula, in the falls and winters of 2001 and 2002. An important component of the research involved the development and verification of methods for extracting estimates of ecologically-meaningful quantities from measurements of scattered sound. The distribution of acoustic volume backscattering at the single frequency of 120 kHz was first examined as an index of the overall biomass of zooplankton. Distinct spatial and seasonal patterns were observed that coincided with advective features. Improved parameterization was then achieved for a theoretical model of Antarctic krill target strength, the quantity necessary in scaling measurements of scattered sound to estimates of abundance, through direct measurement of all necessary model parameters for krill sampled in the study region and survey period. (cont.) Methods were developed for identifying and delineating krill aggregations, allowing the distribution of krill to be distinguished from that of the overall zooplankton community. Additional methods were developed and verified for estimating the length, abundance, and biomass of krill in each acoustically-identified aggregation. These methods were applied to multi-frequency acoustic survey data, demonstrating strong seasonal, inter-annual, and spatial variability in the distribution of krill biomass. Highest biomass was consistently associated with regions close to land where temperatures at ...